Comparison of performance of different optimal cerebral perfusion pressure parameters for outcome prediction in adult traumatic brain injury: a collaborative European neurotrauma effectiveness research in traumatic brain injury (CENTER-TBI) study - Zeiler, Frederick A.; Ercole, Ari; Cabeleira, Manuel; Carbonara, Marco; Stocchetti, Nino; Menon, David K.; Smielewski, Peter; Czosnyka, Marek; Sakowitz, Oliver; Younsi, Alexander (Journal of neurotrauma, 2019)
It has been postulated previously that individualized cerebral perfusion pressure (CPP) targets can be derived from cerebrovascular reactivity indices. Differences between real CPP and target CPP (named generically optimal CPP) has been linked to global outcome in adult traumatic brain injury (TBI). Different vascular reactivity indices can be utilized in the determination. The goal of this study is to evaluate CPPopt parameters, derived from three intracranial pressure (ICP)-derived cerebrovascular reactivity indices, and determine which one is superior for 6- to 12-month outcome prediction. Using the prospectively collected data from the Collaborative European NeuroTrauma Effectiveness Research in TBI (CENTER-TBI) study, the following indices of cerebrovascular reactivity were derived: pressure reactivity index (PRx; correlation between ICP and mean arterial pressure [MAP]), pulse amplitude index (PAx; correlation between pulse amplitude of ICP [AMP] and MAP), and RAC (correlation between AMP and CPP). CPPopt was derived using each index. Univariate logistic regression models were created to assess the association between CPPopt with global dichotomized outcome at 6 to 12 months, as assessed by Glasgow Outcome Score-Extended. Models were compared via area under the receiver operating curve (AUC) and Delong's Test. A total of 204 patients had available data. CPPopt derived from PRx, PAx, and RAC performed variably in their association with outcomes. PRx- and RAC-based CPPopt performed similarly, with RAC parameters trending towards highest AUC values. PAx-based CPPopt parameters failed to reach significant associations with dichotomized outcomes at 6 to 12 months. CPPopt parameters derived from PRx and RAC appear similar in their overall ability for 6- to 12-month outcome prediction in moderate/severe adult TBI.